Comorbidities, long‐term outcome and poststroke epilepsy associated with ischemic stroke – A multicenter observational study of 125 dogs - Cecilia‐Gabriella Danciu; Rita Gonçalves; Carrete Jordina Caldero; Christoforos Posporis; Javier Espinosa; Steven deDecker; Hanne Gredal; Sophie Elizabeth Wyatt (Journal of Veterinary Internal Medicine)
Abstract Background Little is known regarding the comorbidities and prognostic factors associated with the long‐term outcome of ischemic stroke in dogs. Although poststroke epilepsy is a well‐recognized syndrome in people, it is unclear if this phenomenon also occurs in dogs. Hypothesis/objective Document comorbidities, long‐term outcome (survival and stroke recurrence), and occurrence of epileptic seizures associated with ischemic stroke. Animals One hundred and twenty‐five client‐owned dogs. Methods Multicenter observational study including dogs diagnosed with ischemic stroke between 2000 and 2021. Associations between comorbidities, stroke location and extent, poststroke epileptic seizures, and long‐term outcome were investigated. Referring veterinarians and owners were contacted to obtain follow‐up information. Results Fifty‐two dogs (41.6%) had a comorbidity. The most common comorbidities were hypertension (20%) and proteinuria (8%). Eight dogs (6.4%) that did not survive to discharge had a territorial ischemic stroke. Overall median survival time for dogs with a comorbidity was 482 days (range, 1‐3013) and 907 days (range, 1‐3027) in dogs without comorbidities (Kaplan‐Meier survival analysis P = .602). Twenty‐four dogs (19.2%) had a suspected stroke recurrence and a total of 8/109 dogs (7.3%) developed poststroke epilepsy. No association was found between suspected stroke recurrence or development of poststroke epilepsy and survival (P = .812, P = .487). Conclusions and Clinical Importance Despite no significant difference in survival of dogs diagnosed with ischemic stroke, with or without comorbidities, investigations for underlying causes are recommended to provide appropriate treatment. Poststroke epilepsy is uncommon.